Hybrid time slots sequencing model for a class of scheduling problems - Castro, Pedro M. (2012)
This article presents a new model for the short-term scheduling of multistage batch plants with a single unit per stage, mixed storage policies, and multiple shared resources for moving orders between stages. Automated wet-etching stations for wafer fabrication in semiconductor plants provide the industrial context. The uncommon feature of the continuous-time model is that it relies on time grids, as well as on global precedence sequencing variables, to find the optimal solution to the problem. Through the solution of a few test cases taken from the literature, we show that new model performs significantly better than a pure sequencing formulation and better than a closely related hybrid model with slightly different sequencing variables. We also propose a new efficient heuristic procedure for extending the range of problems that can effectively be solved, which essentially solves relaxed and constrained versions of the full-space model.